Initiating The Future Of Dawah (Study Of Manara Studios Innovative Strategy In Reaching Out Alpha Generation) - Farabi, Ahmad (Riwayat: Educational Journal of History and Humanities, 2024)
This research explores the innovative digital da'wah strategy implemented by Manara Studios, Jakarta, aimed at Generation Alpha. Through comprehensive analysis, this study highlights the studio's approach to revitalizing digital da'wah, Generation Alpha segmentation, content and product development, and adaptation to cultural changes and trends. Manara Studios leverages digital platforms, social media research, and quantitative surveys to create engaging, educational content that speaks to Generation Alpha's unique preferences. This study emphasizes the importance of integrating current trends with Islamic teachings to design content that is interesting and spiritually enriching for the generation born in the digital era. This Manara Studios case study offers valuable insight into effective digital da'wah strategies for reaching and influencing Generation Alpha.